Spain : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2011)
Rebalancing in Spain's private sector is under way, but with more modest progress on reducing stocks. Spain is subject to significant spending pressures, reflecting unfavorable demographic trends and subdued growth prospects, and will require substantial structural reform. Priority reforms are needed to strengthen its fiscal framework. The study tries to infer the potential impact of the ongoing integration process on bank efficiency based on preconsolidation bank data. The reforms, such as those recently implemented, of employment protection and collective bargaining could help improve Spain's inflation performance.